THE CAUSAL IMPACT OF ISLAMIC FINANCIAL INCLUSION ON HUMAN DEVELOPMENT: A REGRESSION DISCONTINUITY ANALYSIS OF INDONESIAN PROVINCES - Annisa Maulidia Alfian; Ahmad Wira; Nora Zulvianti (UIN Sunan Gunung Djati Bandung, 2026)
This study examines whether Islamic financial inclusion contributes to improvements in the Human Development Index (HDI) in Indonesia during the period 2020–2024. While previous studies generally report positive associations between financial inclusion and development outcomes, evidence regarding whether Islamic financial inclusion improves human development remains limited, particularly from a causal perspective and in the context of regional disparities. To address this gap, this study measures Islamic financial inclusion using the Islamic Financial Inclusion Index (IFII) based on the dimensions of accessibility, availability, and usage following Sarma (2012), and employs a Regression Discontinuity Design (RDD) to provide stronger evidence on its causal impact. The results show that Islamic financial inclusion in Indonesia remains low and uneven across provinces. Most provinces are in the low category, except Aceh, which is classified as high (0.719), and DKI Jakarta as moderate (0.548). The RDD estimation indicates a negative relationship between IFII/IFII and HDI (−4.1893), but no statistically significant discontinuity is found around the cutoff. This finding suggests that improvements in Islamic financial inclusion have not yet translated into measurable gains in human development outcomes during the study period, possibly because the benefits of financial inclusion require longer adjustment periods and supportive structural conditions before being reflected in HDI indicators.These findings indicate that financial inclusion alone may be insufficient to improve human development outcomes. Its effectiveness appears to depend on complementary factors such as financial literacy, infrastructure quality, institutional capacity, and the productive utilization of financial services.